The Need for Intervention for Psychological Well-Being (PsWB) of Gen-Y Employees in Selected Business Process Outsourcing in the Philippines - Eunice Mareth Querol Areola, Phd HSG; Irvin Recto Perono; Joan Camille Ilagan (Sekolah Tinggi Manajemen IPMI, 2021)
The study is descriptive correlation. Using Ryff’s scale for Psychological Well-Being, the relationship of demographics – age, tenure in the company and the years of experience in the BPO industry were statistically analysed using correlation. Relationship amongst the dimensions of PsWB were also tested. Only age has a positive significant relationship with the dimensions of PsWB to be specific – Autonomy, Environmental Mastery and Positive Relations to Others but to a weak extent only. Statistical analysis showed that there was a significant relationship between the six dimensions of PsWB with a positive high correlation.